Data from: Y chromosome haplotype distribution of brown bears (Ursus arctos) in Northern Europe provides insight into population history and recovery (Ursus arctos) - Schregel, Julia; Eiken, Hans Geir; Grøndahl, Finn Audun; Hailer, Frank; Aspi, Jouni; Kojola, Ilpo; Tirronen, Konstantin; Danilov, Pjotr; Rykov, Alexander; Poroshin, Eugene; Janke, Axel; Swenson, Jon E.; et al. (Zenodo, 2015)
High-resolution, male-inherited Y-chromosomal markers are a useful tool for population genetic analyses of wildlife species, but to date have only been applied in this context to relatively few species besides humans. Using nine Y-chromosomal STR and three Y-chromosomal single nucleotide polymorphism markers (Y-SNPs), we studied whether male gene flow was important for the recent recovery of the brown bear (Ursus arctos) in Northern Europe, where the species declined dramatically in numbers and geographic distribution during the last centuries but is expanding now. We found 36 haplotypes in 443 male extant brown bears from Sweden, Norway, Finland and Northwestern Russia. In 14 individuals from southern Norway from 1780 to 1920, we found two Y chromosome haplotypes present in the extant population as well as four Y chromosome haplotypes not present among the modern samples. Our results suggested major differences in genetic connectivity, diversity, and structure between the eastern and the western populations in Northern Europe. In the west, our results indicated that the recovered population originated from only four male lineages, displaying pronounced spatial structuring suggestive of large-scale population size increase under limited male gene flow within the western subpopulation. In the east, we found a contrasting pattern, with high haplotype diversity and admixture. This first population genetic analysis of male brown bears shows conclusively that male gene flow was not the main force of population recovery. Y-STR data, Y-SNP data and geographic location of brown bears in Northern Europe This data file contains sample names (indicating the sampling location used to group samples for the analyses) and the respective Y-STR and Y-SNP haplotypic profile for each individual as well as the assigned Y chromosomal haplotype. In addition, each sample is given the samling country and the sampling coordinates in decimal format. Datafile_DRYAD.xlsx